Redescription of five Amazonian species of Ctenus Walckenaer (Araneae, Ctenidae, Cteninae) - Polotow, Daniele; Brescovit, Antonio D. (Zootaxa, 2012)
Five species of Ctenus from the Amazon basin are redescribed: C. delesserti (Caporiacco, 1947), C. falconensis Schenkel,1953, C. nigritus F.O. Pickard-Cambridge, 1897, C. serratipes F.O. Pickard-Cambridge, 1897 and C. sigma (Schenkel, 1953).Three new synonymies are proposed: Ctenus fulvipes Caporiacco, 1947, C. itatiayaeformis Caporiacco, 1955 and C. scenicusCaporiacco, 1947 with C. serratipes. The female of Ctenus nigritus is described for the first time. The distributional ranges of Ctenus nigritus and C. serratipes are extended. We also present distributional maps of the five redescribed species.